Defining Community Food Security - Alison E. Lutz; Mickie E. Swisher; Mark A. Brennan (EDIS, 2007)
AEC-383, a 4-page fact sheet by Lutz, A.E., Swisher, M.E., and Brennan, M.A., provides background and history of the concept of community food security. Includes references. Published by the UF Department of Agricultural Education and Communication, May 2007.